Managing the transition to a more compact city in Australia. Issue 4 (2nd October 2017) - Bunker, Raymond; Crommelin, Laura; Troy, Laurence; Easthope, Hazel; Pinnegar, Simon; Randolph, Bill
ABSTRACT: This paper explores the transition towards the compact city model in Australia, which has become the orthodoxy of metropolitan planning in the last two decades. This transition is aligned with neoliberal policies through which private investment and the marketplace have become dominant in driving urban growth and change. However, an intensive review of the experience of Sydney and Perth shows that a metanarrative of transition from a social-democratic to a neoliberal form in metropolitan planning is an oversimplification, and blurs the redeployment of state powers, processes and institutions to address new challenges. The paper explores two related points. First, it demonstrates how a methodical examination of the eclectic mixture of policies designed to drive the compact city transition can enable the identification and analysis of shared policy trends across the two cities. These trends relate to metropolitan strategies, transport planning, infrastructure funding, centralization and local input. Second, it demonstrates how such a review can also provide broader insights into the contours of the political economy of the compact city, and the potential significance for its citizenry. Key insights relate to who has a say in development control, growing executive power, increased government engagement with lobby groups and growing inequality.